HAS EXCHANGE RATE VOLATILITY PRODUCED ANY EFFECTS ON BILETERAL AND SECTORAL EXPORTS IN EUROPE? NEW EVIDENCE FROM THE UNITED KINGDOM - Serenis, Dimitrios; Serenis, Paul (Вісник Економіки, 2017)
This paper examines the effect of exchange rate volatility to sectoral- bilateral exports for a set of eleven European countries to a exports during the period of 1973 -2008. Our investigation on the topic has examined one very important aspect. In other words, it is possible for the same set of countries to produce different results when different trade flows are examined. Further more the results of these trade flows used to examine the overall aggregate effects. Our investigation on bilateral sectorial trade flows has been preformed in two ways. The first incorporated the utilization of total U.K. to E.U. -14 exports for each sector while the second incorporated each of the U.K. 's to E.U.-14 sectoral flows. Overall our results suggest the existence (for some countries and products) of a mixed relationship which is consistent with our previews empirical work.